The Analysis of Students Scientific Reasoning Ability in Solving the Modified Lawson Classroom Test of Scientific Reasoning (MLCTSR) Problems by Applying the Levels of Inquiry - Novia, N.; Riandi, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
This study aims to determine the students’ achievement in answering modified lawson classroom test of scientific reasoning (MLCTSR) questions in overall science teaching and by every aspect of scientific reasoning abilities. There are six aspects related to the scientific reasoning abilities that were measured; they are conservatorial reasoning, proportional reasoning, controlling variables, combinatorial reasoning, probabilistic reasoning, correlational reasoning. The research is also conducted to see the development of scientific reasoning by using levels of inquiry models. The students reasoning ability was measured using the Modified Lawson Classroom Test of Scientific Reasoning (MLCTSR). MLCTSR is a test developed based on the test of scientific reasoning of Lawson’s Classroom Test of Scientific Reasoning (LCTSR) in 2000 which amounted to 12 multiple-choice questions. The research method chosen in this study is descriptive quantitative research methods. The research design used is One Group Pretest-Posttest Design. The population of this study is the entire junior high students class VII the academic year 2014/2015 in one junior high school in Bandung. The samples in this study are one of class VII, which is class VII C. The sampling method used in this research is purposive sampling. The results showed that there is an increase in quantitative scientific reasoning although its value is not big.